Recovery time and its predictors of severe acute malnutrition among under five children admitted at the therapeutic feeding center of Hiwot Fana comprehensive specialized hospital, eastern Ethiopia, 2024: a semi-parametric model - Meseret, Fentahun; Keneni, Mulualem; Alemu, Ayichew; Tizazu, Diribsa; Alemayehu, Tesfaye Asfaw; Mossie, Yalew; Teshager, Tilahun; Wondimneh, Fenta (Frontiers in Nutrition, 2024)
Background: Early recovery is a performance indicator of quality care for under five children admitted due to severe acute malnutrition at therapeutic feeding center. Despite the available interventions to tackle such nutritional problems, there is scarce information on time to recovery and its predictors among children with severe acute malnutrition in Ethiopia more particularly in the study setting.Objective. The study is aimed at assessing time to recovery from severe acute malnutrition and its predictors among admitted children aged 6-59 months at the therapeutic feeding center of Hiwot Fana comprehensive specialized hospital, eastern Ethiopia, from September 01, 2019 to March 01, 2024.Methods: A retrospective cohort study was conducted at the therapeutic feeding center of Hiwot Fana comprehensive specialized hospital among a randomly selected sample of 349 patients with severe acute malnutrition who were under therapeutic feeding. Data were collected by using a data abstraction tool; then, stored into Epi-data version 4.6 and STATA version 17.0 statistical software. Descriptive statistics, Kaplan Meier plots and median survival times, Log-rank test and Cox-proportional hazard regression were used for reporting the findings of this study. After performing Cox-proportional hazard regression, model goodness-of-fit and assumptions were checked. Finally, the association between independent variables and time to recovery in days was assessed using multivariable Cox Proportional Hazard model and variables with a p-value < 0.05 were considered as statistically significant.Results: Median survival time to recovery among severe acute malnutrition clients was 17 days (95%CI: 16-18).The incidence density recovery rate was 5.7(95%CI: 4.9-6.6) per 100 person-day observation.Factors that affect time to recovery were being from rural residency (AHR=2.072; 95%CI=1.336-3.215), being vaccinated according to their age (AHR=1.848; 95%CI=1.162-2.939) and lack of analgesics administration (AHR=0.685; 95%CI=0.472-0.995).The median survival time to recovery in this study was found to be suboptimal. Residency, vaccination status of the child and analgesics administrations were determinant factors. Giving attention for vaccination coverage, fever and pain management as protocol helps to reduce the length of hospital say by facilitating recovery rate among under five severely malnourished children in Ethiopia.